Salezijanske cerkvene pesmarice - Ferenčak, Štefan Alojzij (Traditiones (Ljubljana), 1999)
After the example of their founder Janez Bosko Salesians educate the young also through music. In the course of their liturgical and pastoral endeavours for a "willful, active and fruitful" cooperation during the worship of God singing and music have been especially important ever since they had come to Slovenia in 1901. To facilitate this between 1930 and mid-1970's they preparedand published at least ten publications of church hymnal texts which soon spread throughout Slovenia. Salesians also collected and published 22 printed collections of hymnals with notes in the period from 1935 to 1980. Three shapirographed collections (Gnus, Mihelčič, Jenko) had a smaller circulation and were intended for choirs. Some publications, among them especially the twenty printed volumes - each containing approximately 40 hymns (Volume 19 contains 112 litanyc responses) - of the Jurčak-Mihelčič collection of hymnals for folk and polyphonic youth singing were printed and reprinted several times, some of them with a very high circulation number. The Jurčak-Mihelčič collection is still invaluable in working with children's and youth choirs.
Keywords: cerkvena glasba; cerkvene pesmarice; cerkvene pesmi